Ischemic Stroke - D'Aliberti, Giuseppe; Longoni, Marco; Motto, Cristina; Oppo, Valentina; Perini, Valentina; Valvassori, Luca; Vidale, Simone (Springer International Publishing : Imprint: Springer, 2017)
This book provides detailed practical guidance on the management of acute ischemic stroke in the clinical settings encountered in daily practice. Real-life cases are used to depict a wide range of clinical scenarios and to highlight significant aspects of management of ischemic stroke. In addition, diagnostic and therapeutic protocols are presented and helpful decision-making algorithms are provided that are specific to the different professionals involved in delivery of acute stroke care and to differing types of hospital facility. The coverage is completed by the inclusion of up-to-date scientific background information relevant to diagnosis and therapy. Throughout, the approach adopted is both practical and multidisciplinary. The book will be of value for all practitioners involved in the provision of acute stroke care, and also for medical students.
Keywords: Medicine.; Emergency medicine.; Neuroradiology.; Neurology.; Neurosurgery.; elektronické knihy; electronic books